prompt
stringlengths
46
55
ground_truth
int64
-10
10
Solve for a in the following equation: -3a - 3 = -3
0
Solve for z in the following equation: 2z - 8 = -10
-1
Solve for x in the following equation: 7x - 2 = 68
10
Solve for y in the following equation: -1y - 7 = -15
8
Solve for x in the following equation: -5x - 3 = -43
8
Solve for c in the following equation: 3c - 10 = -25
-5
Solve for c in the following equation: 7c + 3 = -4
-1
Solve for c in the following equation: 4c + 4 = -20
-6
Solve for a in the following equation: 10a + 5 = -45
-5
Solve for b in the following equation: -7b + 5 = -9
2
Solve for b in the following equation: 10b + 6 = 6
0
Solve for z in the following equation: 2z = -8
-4
Solve for c in the following equation: 6c - 2 = 52
9
Solve for z in the following equation: -8z - 4 = 28
-4
Solve for c in the following equation: 2c - 5 = -13
-4
Solve for z in the following equation: 4z + 6 = -26
-8
Solve for z in the following equation: -3z - 1 = 11
-4
Solve for a in the following equation: -5a + 1 = -29
6
Solve for a in the following equation: -1a - 8 = -1
-7
Solve for z in the following equation: 4z - 9 = -13
-1
Solve for z in the following equation: 10z + 2 = -48
-5
Solve for c in the following equation: -6c + 5 = -1
1
Solve for b in the following equation: -6b - 8 = -62
9
Solve for c in the following equation: 2c + 10 = 12
1
Solve for y in the following equation: -4y - 10 = -14
1
Solve for z in the following equation: -1z - 4 = 2
-6
Solve for z in the following equation: -7z - 10 = -10
0
Solve for y in the following equation: 6y + 5 = 5
0
Solve for x in the following equation: 9x + 7 = -29
-4
Solve for y in the following equation: 3y - 8 = 4
4
Solve for c in the following equation: -4c - 6 = -6
0
Solve for b in the following equation: 7b + 5 = 54
7
Solve for a in the following equation: 3a + 4 = -20
-8
Solve for z in the following equation: -8z - 8 = 48
-7
Solve for z in the following equation: 1z - 3 = 0
3
Solve for c in the following equation: 6c + 5 = 5
0
Solve for a in the following equation: 2a - 2 = -10
-4
Solve for y in the following equation: 7y - 5 = 2
1
Solve for c in the following equation: 6c - 3 = -63
-10
Solve for b in the following equation: 7b - 6 = 64
10
Solve for c in the following equation: -3c + 4 = -2
2
Solve for a in the following equation: 2a + 4 = -12
-8
Solve for c in the following equation: -2c + 8 = 22
-7
Solve for c in the following equation: -7c - 2 = -44
6
Solve for a in the following equation: -5a - 1 = 44
-9
Solve for c in the following equation: -2c - 6 = 10
-8
Solve for z in the following equation: 1z - 5 = -11
-6
Solve for b in the following equation: -8b - 8 = -32
3
Solve for y in the following equation: -9y - 9 = -45
4
Solve for c in the following equation: -6c - 4 = -40
6
Solve for y in the following equation: 3y + 6 = 36
10
Solve for c in the following equation: -7c - 2 = 40
-6
Solve for a in the following equation: 7a + 7 = -7
-2
Solve for z in the following equation: 6z + 9 = -21
-5
Solve for b in the following equation: -4b - 3 = -43
10
Solve for a in the following equation: 8a - 8 = -64
-7
Solve for y in the following equation: 1y + 3 = 8
5
Solve for b in the following equation: -10b + 9 = 69
-6
Solve for b in the following equation: 1b - 6 = -11
-5
Solve for a in the following equation: 6a + 7 = 67
10
Solve for b in the following equation: -6b + 8 = -10
3
Solve for z in the following equation: -1z - 8 = -2
-6
Solve for c in the following equation: 6c + 2 = 38
6
Solve for z in the following equation: -5z + 8 = 48
-8
Solve for z in the following equation: -8z + 5 = 69
-8
Solve for a in the following equation: -6a + 2 = 50
-8
Solve for x in the following equation: 6x + 2 = 50
8
Solve for b in the following equation: -2b - 5 = 7
-6
Solve for y in the following equation: 7y - 9 = 12
3
Solve for y in the following equation: 5y + 8 = 33
5
Solve for b in the following equation: 4b - 1 = -17
-4
Solve for c in the following equation: -4c + 9 = 13
-1
Solve for y in the following equation: 8y + 5 = 5
0
Solve for a in the following equation: 6a + 1 = 37
6
Solve for y in the following equation: 5y + 1 = 11
2
Solve for z in the following equation: -1z - 1 = -9
8
Solve for x in the following equation: 7x - 9 = 33
6
Solve for y in the following equation: 1y - 9 = -1
8
Solve for z in the following equation: 4z + 9 = 33
6
Solve for a in the following equation: -8a - 9 = 39
-6
Solve for y in the following equation: 7y - 9 = -23
-2
Solve for y in the following equation: -4y - 10 = -2
-2
Solve for a in the following equation: 9a + 8 = 35
3
Solve for x in the following equation: 3x + 4 = 22
6
Solve for x in the following equation: -2x - 4 = -12
4
Solve for a in the following equation: -2a + 3 = -5
4
Solve for y in the following equation: -6y = 48
-8
Solve for z in the following equation: -7z - 1 = 20
-3
Solve for x in the following equation: 1x + 1 = -2
-3
Solve for z in the following equation: -9z - 1 = -73
8
Solve for a in the following equation: -2a + 6 = 26
-10
Solve for x in the following equation: 6x + 8 = 20
2
Solve for x in the following equation: 2x + 3 = -5
-4
Solve for z in the following equation: 5z - 7 = -52
-9
Solve for c in the following equation: -6c - 9 = 15
-4
Solve for y in the following equation: 3y + 7 = -8
-5
Solve for y in the following equation: 4y - 4 = -40
-9
Solve for x in the following equation: 3x - 1 = -10
-3
Solve for a in the following equation: -2a + 2 = -10
6
Solve for b in the following equation: -4b - 3 = -39
9